An early evaluation of team consistency and scope optimization in team-based cancer care - Leah K. Lambert; Farinaz Havaei; Scott M. Beck; Andy Ma; John Larmet; Jagbir Kaur; Nassim Adhami; Dan Le; Ryan Woods (BMC Cancer)
Abstract Background The British Columbia (BC) government has made significant investments towards the implementation of team-based care (TBC) in its provincial comprehensive cancer control program. TBC implementation involves purposeful efforts towards: (a) establishing/expanding multidisciplinary care teams, (b) optimizing scope of practice, and (c) increasing care team consistency. Study objectives include an early-phase evaluation of (i) the association between TBC elements and team effectiveness and (ii) staff perceptions of barrier and facilitators of team effectiveness. Methods A series of five surveys over a 2-year period will be administered to prospectively evaluate the ongoing implementation of TBC. This study draws on data from the first of the five planned surveys, administered in May 2023. Eligible respondents included 299 program employees—spanning various roles such as physicians, nurses, and unit clerks—working within TBC at the time of survey deployment. The survey included both validated and researcher-developed questions that were either closed or open-ended, including measures of team composition, team consistency, team effectiveness, scope of practice, and demographics. Quantitative data were analyzed using descriptive and regression analysis; qualitative data were analyzed guided by interpretive description methodology. Results Collected responses totaled 121, with the majority of respondents being women (76%), full-time employees (90%), and working in direct patient care (77%). Regression analyses indicated that (i) higher frequency of consistently working with the same team members and (ii) lower proportion of shifts practicing below scope are both significant predictors of higher team effectiveness ratings. Qualitative data highlighted staffing levels as a driver of under- and over-utilized scopes of practice. Furthermore, effective communication, enhanced knowledge of each team member’s scope of practice, and strong interpersonal relationships were highlighted as contributing factors to effectiveness among multidisciplinary care teams. Conclusions Preliminary findings from the first of five prospective surveys highlight team consistency and role optimization as drivers of effective teamwork in the early implementation of a team-based model of cancer care. Future research should explore contextual factors that influence cancer care staff and clinicians’ perceptions of effectiveness.